Dynamics of transcutaneous oxygen tension at the operations on the aorto-femoral segment distal of the level of aortic compression - A. M. Putintsev; V. V. Voroshilin; V. A. Lutsenko; V. N. Sergeyev; V. I. Rudayev (Acta Biomedica Scientifica)
Estimation of transcutaneous partial pressure of oxygen is the main noninvasive method of evaluation and study microhaemodynamics and tissue blood supply. Aim of the research: to study the dynamics of transcutaneous partial pressure of oxygen at surgery of aortofemoral segment performed more distally of aortic compression. Material and methods: the survey included 49 patients with arterial sclerotic disease of aortofemoral segment with comorbid Ilb-IV stage chronic lower limb ischemia according to Pokrovsky-Fountain classification, and with II-III stage chronic infrarenal abdominal aortic aneurysm according to Pokrovsky classification. The patients' age was 52-76y.o. For the assessment of peripheral microhaemodynamics we used the technique of estimation of transcutaneous partial pressure of oxygen (ТсРО2) with application of multichannel monitor of Radiometer TCM-400 system. The suggested method offers the possibility to evaluate the severity degree of microcirculatory disorders in lower limbs and to assess effectiveness of revascularization process.